OPPORTUNITIES FOR USING ARTIFICIAL INTELLIGENCE TOOLS IN UZBEK LANGUAGE LESSONS - Salisheva Zilola Ismailovna (Modern American Journals, 2025)
This article explores the potential of using artificial intelligence (AI) tools in the teaching and learning of the Uzbek language, especially within the context of higher philological education in Uzbekistan. As the field of education undergoes rapid digital transformation, AI is emerging as a significant tool to support personalized learning, automate assessment, and enhance linguistic competence. The study examines various AI applications, including intelligent tutoring systems, AI-based writing assistants, and natural language processing platforms, and evaluates their relevance to Uzbek language instruction. The article also discusses pedagogical challenges and practical implications associated with integrating these technologies into language curricula. By analyzing global trends and local realities, the study provides a comprehensive overview of AI’s role in transforming traditional Uzbek language education.
Keywords: Uzbek language, artificial intelligence, language instruction, digital pedagogy, AI tools, personalized learning, natural language processing, higher education, philological education.